Kualitas Pelayanan Bank Jateng Terhadap Pembayaran UKT Mahasiswa - Nazwa, Nurissa Shifakhul; Khasanah, Kholifatul; Hilmy, Muhamad Ikhsanul; Natasya, Berliana Ayu; Febriana, Annisa; Nugraha, Joko Tri (ANTASENA: Governance and Innovation Journal, 2026)
This study aims to analyze the quality of Bank Jateng's services in supporting the payment of Single Tuition Fees (UKT) for Tidar University students using the SERVQUAL approach. This study uses a quantitative descriptive method using a random sampling technique on 90 students of the Faculty of Social and Political Sciences, Tidar University, class of 2025. Data were collected using a questionnaire with a Likert scale and the data was processed using SPSS version 31 to produce frequencies, percentages, and average values for each indicator. The results of the study showed that most respondents gave positive assessments to all service dimensions, especially in the aspects of empathy, responsiveness, and assurance with a satisfaction level reaching 86.7%. Indicators that meet student expectations include facilities, clarity of information, service skills, and transaction security. Good service quality plays a direct role in student satisfaction and trust 1 as service users. However, improvements to the system aspect are still needed to minimize transaction errors. Consequently, optimal service can increase the efficiency of educational administration and user loyalty to Bank Jateng services.